THE ADAPTIVE MANAGEMENT DEVELOPMENT FOR THE ENTERPRISE’S STRATEGIC COSTS UNDER THE FOURTH INDUSTRIAL REVOLUTION CONDITIONS - OSTRININA, OLENA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Modern enterprises operate under the fourth industrial revolution conditions, which are characterized by radical changes in production processes through digitalization, big data processing, and cyber-physical systems usage. At the same time, accelerating the market environment's transformations requires the business entities to adapt to the changes of the environmental conditions. With this transformation in mind, the purpose of the article is to form a theoretical and methodological basis for the industrial enterprises' strategic cost management organization. The semantic analysis results of the "cost management" concept interpretations, performed by using the Advego keyword search system, have been used as a basis for achieving the article goal. The cost management objects systematization has been carried out. The ways to such objects decomposition for management purposes has been justified. The additional cost management objects, such as the company's presence parameters in the value creation network, characteristics of the enterprise's strategic choice, the company's business model elements, the company's element architectural description, have been offered. The selection of cost management objects has determined the author's hypothesis about the need to add strategicity to the cost management circuits, which should be implemented on an ongoing basis and in expanding the cost management circuits' adaptive properties. The following classification features have been introduced as part of the control object's decomposition: strategic costs, critical costs, and costs adaptability. The description of the cost management system corresponded with the fourth industrial revolution features has been given by the cost management subject structuring and the elements of the cost management system systematization. The contours allocation of tactical and strategic adaptation to business conditions changes within the enterprise's cost management system has been proposed.
Keywords: adaptive management; cost; strategic costs; cost management; management system